Further evidence for the existence of broiler chicken PFN (pale, firm, non-exudative) and PSE (pale, soft, exudative) meat in brazilian commercial flocks - CARVALHO,Leila Moreira de (2018)
Abstract This work aims to investigate the incidence of two color abnormalities in broiler meat: PFN (Pale, Firm, Non-exudative) and PSE (Pale, Soft, Exudative), as well as the physicochemical alterations promoted by those anomalies. The samples of broiler breast meat (n = 700) were classified as Normal (44<L*<53, pH>5.8), PSE (L*≥53, pH<5.8) and PFN (L*≥53; pH>5.8). The occurrence of Normal, PSE and PFN samples was 69%, 11% and 20%, respectively. PFN samples presented a 4.2% higher water-holding capacity compared to PSE meat. PSE meats displayed a higher MFI (89.4) when compared to PFN and Normal meats. It was also noticed that the levels of lipid oxidation were greater in PSE breasts compared to Normal breasts. The total carbonyl in PFN, Normal and PSE meats was 8.2, 7.4 and 5.7 nmol/mg proteins, respectively. These results confirm the existence of a PFN anomaly in broiler breast meat, which presents functional properties similar to the Normal group. In addition to that, the less firm texture displayed by PSE meats is the result of a greater proteolytic activity, which seems to be related not only to the activation of the calpains, due to the excessive Ca 2+, but also to the lower level of protein oxidation.